Prolonged enhancement of anterior thalamic synaptic responsiveness by stimulation of a brain-stem cholinergic group - Pare, D (J Neurosci, 1990)
This study describes the effects of brain-stem cholinergic laterodorsal tegmental (LDT) stimulation on the synaptic responsiveness of anterior thalamic (AT) neurons. A sample of AT cells, physiologically identified by their short-latency (less than 6.5 msec) response to mammillary body (MB) stimulation, was recorded in unanesthetized, chronically implanted cats and in urethane-anesthetized cats. In chronic experiments, LDT stimulation evoked a short-latency (10–20 msec) excitation in most AT cells. Moreover, brief LDT trains (3 shocks at 300 Hz, every 3 sec) enhanced the responsiveness of AT cells to both MB (orthodromic) and cortical (ortho- and antidromic) stimuli. This effect did not vary as a function of the interval between LDT conditioning and MB or cortical testing shocks, but as a function of the number of trials. The effects of LDT stimuli resisted reserpine treatment (0.75 mg/kg), suggesting that they were not dependent on the coactivation of monoaminergic fibers. Finally, LDT trains did not suppress inhibitory processes in AT neurons when conditioning-testing intervals were longer than 60 msec. Intracellular recordings performed in urethane-anesthetized cats revealed that LDT stimulation induced a short-latency depolarization which increased with membrane hyperpolarization and was associated with an increase in apparent membrane conductance. Usually, isolated LDT trains did not evoke lasting changes in membrane potential or conductance. However, when LDT trains were applied every 3 sec, they gradually decreased the apparent membrane conductance without altering the membrane potential. This conductance change had a time course similar to the LDT-induced potentiation of responsiveness observed in the chronic experiments. In some neurons, LDT conditioning trains also induced a marked increase in the probability of fast prepotentials being triggered by subthreshold MB or cortical orthodromic volleys. In order to distinguish the cumulative effects of repeated LDT trains from the possibly slow time course of LDT influences, we studied the effects of a unique 1 sec LDT train (at 30 Hz) on the synaptic responsiveness of AT cells recorded extracellularly in reserpine-treated, urethane- anesthetized animals. Such LDT trains induced a 2.9-fold increase in synaptic responsiveness, reaching its peak 40–50 sec after the LDT train and lasting up to 4 min. Iontophoretic application of the muscarinic blocker scopolamine blocked these long-lasting potentiating effects of LDT stimuli. Removal of cortical and basal forebrain inputs to the AT nuclear complex by appropriate transections did not abolish the potentiating effects of LDT trains.(ABSTRACT TRUNCATED AT 400 WORDS)